Kekerasan Dalam PendidikanSebuah Survei atas Praktek Pendidikan di Flores NTT - Rianto Adi (Respons: Jurnal Etika Sosial, 2009)
Violence is a real fact that can be described into many forms: physical, emotional,sexual. This article describes the way the people of Flores think about it and justify it intoeducational action. The survey considers that although violence can be tolerated, the people ofFlores implicitly refused violence for the sake of their future generation.